Beyond Intelligence: The Power of Grit in Achieving Cognitive Excellence Achievement in Chemistry for Sustainable Education - Abukasim, Sudarto M.; Annisa, Desfi; Sutrisno, Hari; Rohaeti, Eli; Dahlan, Jafar (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
Academic achievement is often associated with cognitive ability; however, non-cognitive skills, such as grit, also play an important role in determining learning outcomes. Chemistry is a challenging subject because of the many abstract concepts that require perseverance and dedication to comprehend. This study aimed to examine the relationship between grit and students' cognitive achievement in chemistry learning at the secondary school level, as well as to evaluate the extent to which grit affects learning success. The method used was quantitative, with a survey approach of 200 students in class X in Pekanbaru, Indonesia. The research instruments consisted of a talent questionnaire and a multiple-choice test to measure cognitive chemistry achievement. The data were analyzed using the Pearson product-moment correlation technique after performing prerequisite tests, including normality and homogeneity tests. The results of the analysis showed a significant positive correlation between grit and cognitive achievement (p = 0.001 < 0.05), with a correlation coefficient of 0.234, which is classified as low. These findings indicate that students with higher grit levels tend to have better cognitive performance in chemistry learning, although other factors also play roles. In addition, this study is in line with the Sustainable Development Goal concerning Quality Education, particularly through its focus on the role of non-cognitive skills in learning.